2009
DOI: 10.2118/09-09-16-cs
|View full text |Cite
|
Sign up to set email alerts
|

Conformance Control of CSS and Steam Drive Process With a Carbamide Surfactant

Abstract: Based on physical modelling, this paper discusses the feasibility of injecting additives to control the conformance of the cyclic steam stimulation (CSS) and steam drive processes in the Biquan 10 Block of the Henan Oil Field. The lab test results show that waterflooding with the addition of a carbamide surfactant can decrease residual oil saturation by 4.7% and that steam drive with the addition of this same surfactant can improve the sweep volume and increase the oil recovery factor by 17.5%. Also, field app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…With the relative rotation between the rings, the liquid flows from one gap to another, and has been to the seal edge and thus leakage. According to the literature [6,7], it showed that the surface roughness and the end face gap are in the same order of magnitude. Consequently, the surface roughness is the most important surface geometrical feature of the sealing performance, and can be expressed by extracting the contour surface of a certain region on the surface.…”
Section: Surface Morphology Test For the Seal Facementioning
confidence: 99%
“…With the relative rotation between the rings, the liquid flows from one gap to another, and has been to the seal edge and thus leakage. According to the literature [6,7], it showed that the surface roughness and the end face gap are in the same order of magnitude. Consequently, the surface roughness is the most important surface geometrical feature of the sealing performance, and can be expressed by extracting the contour surface of a certain region on the surface.…”
Section: Surface Morphology Test For the Seal Facementioning
confidence: 99%
“…The experimental results showed that the petroleum sulfonate surfactant can withstand thermal decomposition and substantially increase the oil recovery factor. Zhang et al 21 discussed the advantages of adding carbamide to the steam drive oil recovery technique in both laboratory and field scales. The authors concluded that sweep efficiency was improved in contrast to the conventional steam drive, as a result of which oil recovery factor was increased by 17.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been carried out to understand the reservoir heterogeneity, both for lithology and rock mechanics. Moreover, the literature has proposed some useful strategies to improve the steam conformance, such as high-temperature gas foam with steam [8,9], an oil viscosity reducer or solvent to increase the injection capacity and reduce the fractures [10][11][12], and thermoreversible gel to plug the steam channels [13]. Polymer gels are potential plug agents to solve near wellbore issues.…”
Section: Introductionmentioning
confidence: 99%